Mergers and its Effects in Select Indian Iron and Steel Companies - A Study - Madhumita Dasgupta (Management Journal for Advanced Research, 2022)
As an important sphere of corporate strategy, Mergers and Acquisitions have been undergoing a sea change within the economic set -up since liberalization in India. Massive growth in both Foreign Direct Investment and Foreign Institutional Investors has been witnessed by the economy. Rather than Greenfield Investment, a substantial fraction of the growth in FDI during the late 1990s tends to rapid increase of cross-border deals in form of Mergers and Acquisitions. This study has attempted to identify the performance of some selected Indian Iron and Steel Companies as a regime study through applying techniques like Economic Value Added and Operating Profit.